Moral Orientation Dynamics in Adolescence and Youth - Molchanov S.V.; Markina O.S. (Психологическая наука и образование (2007. Online), 2015)
The problem of moral development is actual for modern psychology. Modern conception of moral development defines two main principles in the basis of moral orientation: care principle and justice principle. Adolescence and youth are sensitive period to develop moral orientation. 139 subjects from three age groups: young adolescents, older adolescents and youth took part in the investigation. Results shows age dynamic of moral judgments preferences, moral dilemma solving with different levels of motivation to achieve and be approved.